2011
DOI: 10.3899/jrheum.101254
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients with Biopsy-proven Giant Cell Arteritis: A South Australian Population-based Study

Abstract: Our population-based cohort study did not demonstrate any increased mortality risk for patients diagnosed with biopsy-proven GCA. The risk of death from infection early in the disease may be increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 11 publications
5
20
1
Order By: Relevance
“…Patients with GCA were also found to have increased rates of mild-moderate infections diagnosed and treated at an outpatient visit and acute upper respiratory tract infections (data not shown). These data underline the risks for infection among patients with GCA, and the concerns for infection-related mortality (24).…”
Section: Discussionmentioning
confidence: 71%
“…Patients with GCA were also found to have increased rates of mild-moderate infections diagnosed and treated at an outpatient visit and acute upper respiratory tract infections (data not shown). These data underline the risks for infection among patients with GCA, and the concerns for infection-related mortality (24).…”
Section: Discussionmentioning
confidence: 71%
“…However, the mortality was higher early in the disease course, especially in patients younger than 70 years at time of diagnosis. Most previous studies showed no increase in mortality compared with the general population,13 including studies of patients with biopsy-proven GCA from Gothenburg14 and Australia 17. Increased mortality was previously reported in studies from Denmark16 and northern Sweden,30 in the latter, mainly due to cardiovascular disease.…”
Section: Discussionmentioning
confidence: 82%
“…However, despite the serious consequences of GCA and the required high‐dose corticosteroid therapy, the mortality rate is generally reported to be equal to the general population . A recent study of mortality in South Australian biopsy‐proven GCA patients reported no significant differences in mortality between GCA patients and the general South Australian population, after adjusting for age and gender .…”
Section: Discussionmentioning
confidence: 99%